PENGEMBANGAN MODEL PEMBELAJARAN SEJARAH BERBASIS SITUS SEJARAH LOKAL DI SMA NEGERI 5 KOTA TERNATE - GAZALI FAR-FAR (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2020)
The teaching and learning model is the basis for implementing learning and is designed based on the result of analyzing curriculum implementation in the classroom. The conceptual reference that outlines the systematic stages for organizing learning experiences to lead to learning objectives. Understanding history is a combination of learning and teaching. Because the effort to study past events certainly has a correlation with current life. Therefore, it is expected that the use of learning history, including the use of local historical sites, can encourage students’ learning interest which can prove by increasing motivation and learning achievement. Based on the result of research conducted, it can be described as follows: 1. Developing a history learning model based on the use of local historical sites can improve the quality of learning. 2. Local historical sites can be developed as effective learning resources .